2018
DOI: 10.1021/acscatal.8b00806
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Frustrated Lewis Pair Chemistry through Robust Gold@N-Doped Carbon for Selective Hydrogenation of Alkynes

Abstract: Pyrolysis of Au(OAc) 3 in the presence of 1,10phenanthroline over TiO 2 furnishes a highly active and selective Au nanoparticle (NP) catalyst embedded in a nitrogen-doped carbon support, Au@N-doped carbon/TiO 2 catalyst. Parameters such as pyrolysis temperature, type of support, and nitrogen ligands as well as Au/ligand molar ratios were systematically investigated. Highly selective hydrogenation of numerous structurally diverse alkynes proceeded in moderate to excellent yield under mild conditions. The high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 78 publications
4
67
0
3
Order By: Relevance
“…Furthermore, both samples show a difference between the Fe 2p 3/2 main peak and the satellite peak of approximately 8.0 eV for Fe 3 O 4 and 7.6 eV for Fe 3 O 4 @N‐doped, which are centered at approximately 718.3 and 717.3 eV for Fe 3 O 4 . The high‐resolution XPS spectra of N 1s (Figure B) shows three peaks of N‐doped graphene mainly corresponding to a quaternary graphitic‐N species (401 eV), along with a pyrrole‐like configuration (400 eV) and N in pyridine oxide species (402.7 eV), which verifies the incorporation of nitrogen into the carbon species. The main O 1s peak (Figure C) for the Fe 3 O 4 sample is at approximately 529.6 eV and is consistent with O coming from the Fe 3 O 4 structure, whereas in the Fe 3 O 4 @N‐doped graphene, the intensity is lower due to its recovery by carbonaceous sheets.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, both samples show a difference between the Fe 2p 3/2 main peak and the satellite peak of approximately 8.0 eV for Fe 3 O 4 and 7.6 eV for Fe 3 O 4 @N‐doped, which are centered at approximately 718.3 and 717.3 eV for Fe 3 O 4 . The high‐resolution XPS spectra of N 1s (Figure B) shows three peaks of N‐doped graphene mainly corresponding to a quaternary graphitic‐N species (401 eV), along with a pyrrole‐like configuration (400 eV) and N in pyridine oxide species (402.7 eV), which verifies the incorporation of nitrogen into the carbon species. The main O 1s peak (Figure C) for the Fe 3 O 4 sample is at approximately 529.6 eV and is consistent with O coming from the Fe 3 O 4 structure, whereas in the Fe 3 O 4 @N‐doped graphene, the intensity is lower due to its recovery by carbonaceous sheets.…”
Section: Resultssupporting
confidence: 67%
“…Brief representation of the methodology to synthesize the Fe 3 O 4 nanoparticles via coprecipitation method following a thermal treatment in presence of 1,10 phenanthroline to finally obtain Fe 3 O 4 @N-doped graphene. [36,37] in pyridine oxide species (402.7 eV), [42,43] which verifies the incorporation of nitrogen into the carbon species. The main O 1s peak (Figure 1 C) These hydroxyl/carbonate species might also come from a carbon coating on the iron oxide.…”
Section: Chemical Structural and Morphological Characterizationmentioning
confidence: 80%
“…The Rossi group recently reported that phenylacetylene partial hydrogenation occurs via heterolytic H 2 activation on Au modified with an N‐functionalized base . A kinetic isotope effect of 2.7 was measured along with a Hammett plot with a negative slope .…”
Section: Discussionmentioning
confidence: 99%
“…The Rossi group recently reported that phenylacetylene partial hydrogenation occurs via heterolytic H 2 activation on Au modified with an N‐functionalized base . A kinetic isotope effect of 2.7 was measured along with a Hammett plot with a negative slope . The 1‐octyne hydrogenation kinetics we observe are also consistent with this Hammett study if alkene reductive elimination or proton transfer to a formal carbanion is rate determining.…”
Section: Discussionmentioning
confidence: 99%
“…While the 1‐hexyne hydrogenation activity is independent on the activation temperature and consequent Au speciation, a volcano‐like curve is observed in the case of 2‐methyl‐3‐butyn‐2‐ol. In accordance with the literature reports, all these gold systems give essentially full selectivity to the aimed alkenes. In addition, HAADF‐STEM examination on the two extreme Au/NC‐ T catalysts confirmed that the atomic dispersion of gold remains unaltered after the hydrogenation performance (Figure S10).…”
Section: Figurementioning
confidence: 99%